2019
DOI: 10.3390/medicina55120777
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl Rosmarinate Prevents the Impairment of Vascular Function and Morphological Changes in L-NAME-Induced Hypertensive Rats

Abstract: Background and Objectives: The potent, endothelium-independent, vasorelaxant effect of ethyl rosmarinate, an ester derivative of rosmarinic acid, makes it of interest as an alternative therapeutic agent for use in hypertension. This study was designed to investigate the effect of ethyl rosmarinate on N ω -nitro-L-arginine methyl ester (L-NAME)-induced hypertensive rats. Materials and Methods: L-NAME was given orally to male Wistar rats for 6 weeks to induce hypertension concurrently with treatment of ethyl ros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…ER, a natural active ingredient in Labiatae plants such as Salvia chinensis and Perilla frutescens, is increasingly concerned by researchers due to its excellent pharmacological effects. Previous research indicated that ER had anti-inflammation [14], anti-oxidation [15], anti-hypertension [16] and neuroprotective activity [17]. Although ER could be applied to treat some diseases, the role of ER against UC has not been fully reported or elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ER, a natural active ingredient in Labiatae plants such as Salvia chinensis and Perilla frutescens, is increasingly concerned by researchers due to its excellent pharmacological effects. Previous research indicated that ER had anti-inflammation [14], anti-oxidation [15], anti-hypertension [16] and neuroprotective activity [17]. Although ER could be applied to treat some diseases, the role of ER against UC has not been fully reported or elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, compared with rosmarinic acid, ethyl rosmarinate (ER, CAS: 174591-47-0) showed better anti-inflammatory activity [14]. Besides, ER was also reported to have other activities such as anti-oxidation [15], antihypertension [16] and neuroprotective activity [17]. For example, ER showed an ability to inhibit LPS-induced NO and prostaglandin E2 production in alveolar macrophages [14].…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that endothelial dysfunction occurred in this animal model. As several studies have reported, the major contribution of L-NAME-induced hypertension is vascular dysfunction [ 4 , 42 ]. Sympathetic nerve overactivity was observed as the contractile response to EFS was increased, but not to exogenous NE in the hypertensive group.…”
Section: Discussionmentioning
confidence: 99%
“…Depletion of NO by Nω-nitro-L-arginine methyl ester (L-NAME), a non-specific nitric oxide synthase (NOS) inhibitor, has been established as a treatment to induce [3]. It has been reported that long-term treatment with L-NAME causes sustained hypertension, cardiovascular dysfunction, and remodeling in animals [4][5][6][7]. Moreover, sympathetic nerve-mediated contractile responses are enhanced in the vasculature isolated from NOS inhibitor-treated rats, which is relevant to a high level of plasma norepinephrine and a low level of plasma NO in these animal models [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Nω-nitro-L-arginine methyl ester (L-NAME) is a chronic inhibitor of NO synthesis, causing endothelial dysfunction and vasoconstriction. This leads to a signi icant increase in blood pressure in rats (Alwi, 2018;Pantan et al, 2019) Based on previous research, the combination of turmeric (Curcuma longa) and gotu kola (Centella asiatica) has a bene icial effect on blood pressure and arterial stiffness (P Hasimun et al, 2019).…”
Section: Introductionmentioning
confidence: 99%